2019
DOI: 10.37358/rc.19.9.7563
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression of Growth Hormone Secretagogue Receptor (GSH-R) of Adipose Tissue Macrophagesin Obese Bariatric Patients

Abstract: Obesity is a major cause of adipose tissue (AT) inflammation. Ghrelin (GHRL), through its growth hormone secretagogue receptor (GHS-R) present on adipose tissue macrophages (ATMs), could modulate AT inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…There is little information about the immunohistochemical expression of GSH-R in human adipose tissues (8). Our current data showed positive immunohistochemical expression of GSH-R associated with CD68-macrophage infiltration in epicardial adipose tissue.…”
Section: Discussionsupporting
confidence: 41%
See 3 more Smart Citations
“…There is little information about the immunohistochemical expression of GSH-R in human adipose tissues (8). Our current data showed positive immunohistochemical expression of GSH-R associated with CD68-macrophage infiltration in epicardial adipose tissue.…”
Section: Discussionsupporting
confidence: 41%
“…In AT, ghrelin through its receptor GHS-R1a may promote adipose tissue inflammation, increased macrophage infiltration, and promoted macrophage polarization to M1 (7). In a previous paper, we showed that adipocyte diameter, ATM accumulation, and immunohistochemical expression of the ghrelin receptor in AT are associated with obesity (8). Ghrelin through its growth hormone secretagogue receptor (GHS-R1a), present on ATMs, may have a pro-inflammatory effect, and deletion of GHS-R1a would decrease the macrophage infiltration in adipose tissue (7,8).…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Ghrelin through its receptor GHS-R1a may promote adipose tissue inflammation, increase macrophage infiltration and promote macrophage polarization to M1 and increase of adipocyte diameter, immunohistochemical expression of the ghrelin receptors in atrial adipose tissue is associated with obesity [25].However, deletion of GHS-R1a would decrease the macrophage infiltration in adipose tissue [26]. Different studies have illustrated the relationship of ghrelin and obesity.It seems that ethnicity has a role in the level of ghrelin, as it was found that ghrelin concentration in obese Caucasians was significantly lower compared to those in their normal weight counterpart compared to Pima Indians [27].While another study explained ghrelin relation with the degree of insulin resistance or diabetes mellitus between obese individuals.…”
Section: Resultsmentioning
confidence: 99%